Konsep Akal Dalam Neurosains Dan Korelasinya Terhadap Pendidikan Di Era Artificial Intelligence (Perspektif Tematik Tafsir Ath-Thabari) - Rizma, Rahma Sivatur; Yusuf, Enjang Burhanudin (LPPM Sekolah Tinggi Ilmu Al-Qur'an Wali Songo Situbondo, 2024)
The mind ('aql) which is united with the brain organ is the only biological organ found only in humans. In the Qur'an, there are many verses related to the activity of the mind, where the verses in the Qur'an that mention the mind can be found in terms related to brain activity. However, in practice, education is still confined to a narrow culture of stigma that the brain and mind are only measured using a numerical intelligence scale. So the availability of verses regarding reason needs to be studied because there is a relevant relationship with brain activity, so in this paper we try to describe in depth the meaning of verses in the Qur'an about neuroscience which mention reason ('aql) to then be integrated into field of Islamic education. This writing method is qualitative with a library research model. This research uses a thematic approach (maudhu'i) based on the perspective of Ath-Thabari interpretation. Data collection comes from literature from books, journals and others related to the topics of interpretation, neuroscience and education. The results of this research, verses from the Qur'an regarding reason can be found in terms determined by brain activity, one of which is tafakkur as stated in Q.S. Al-Baqarah verse 219. In ath-Thabari's interpretation, this verse explains that to meditate or think again about all the good deeds one does, it should be intended to seek Allah's approval, not anything else. The role of educators also needs to play a greater role in maintaining the nature of human thinking in the midst of the Artificial Intelligence (AI) era.